Determination of chitinase activity in different plant samples of Turkey - Arisan-Atac, Inci; Peksel, Aysegul; Yanardag, Refiye (ASIAN JOURNAL OF CHEMISTRY, 2007)
The chitinase activity constitutively present in fruits, vegetables and cereal grains from various healthy plant species growing in Turkey have been determined. Crude extracts from 47 different fruit species, 35 kind vegetables and 4 various cereal grains were tested for chitinase activity using colloidal chitin as a substrat. In general, fruits seem to be the best sources of chitinase activity. The highest activity was found in persimmon fruits and grape berries.
Keywords: chitinase activity; fruit; vegetable; cereal; MOLECULAR-CLONING; ANTIFUNGAL PROTEINS; CLASS-I; PURIFICATION; LEAVES; ENZYMES; ACID; SEED; Chemistry